INTERNATIONAL ASPECTS AND IDENTITY ISSUES OF THE PRINCIPLE OF SELF-DETERMINATION OF PEOPLE THROUGH THE PRISM OF THE PRESPA AGREEMENT (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
The principle of self-determination of people represents the corner stone of internationaL law in base of which international relations between States from the International Community are being regulated. This principle, in spite of being subject of many international documents and declarations, which in virtue of their universality, have already attributed the principle an imperative character, however his observance in international relations is not always guaranteed. Accordingly, seen through the dispositions of the Treaty of Prespa, the principle of self-determination of people that belongs to the Macedonian people, has been frequently violated. The violations refer to different aspects of the principle, beginning from the right to choose its own name, right to own political system, right to history, right to language, right to culture, right to sovereign equality and equal treatment in international relations etc. In base of this, the purpose of the paper is to explore the international aspects and the identity issues of the principle of selfdetermination of people through the prism of the Prespa Agreement.